Planning considerations prior to laryngectomy for a patient infected with severe acute respiratory syndrome coronavirus-2 pre-operatively. Issue 11 (4th November 2020) - Coleman, H; Tikka, T; Okhovat, S; Kang, S K
Abstract: Background: Coronavirus disease 2019 was declared a pandemic on 11th March 2020. All non-urgent surgical procedures have been postponed indefinitely. The British Association of Head and Neck Oncology state that only those with treatable head and neck cancer unsuitable for alternative treatment should undergo surgery. This paper details our management of a patient who tested positive for severe acute respiratory syndrome coronavirus-2 days before curative surgery for laryngeal cancer. Case report: By following British Association of Head and Neck Oncology guidance, a 49-year-old male scheduled for total laryngectomy and bilateral neck dissection for a T3 transglottic squamous cell cancer was pre-operatively identified as an asymptomatic carrier of severe acute respiratory syndrome coronavirus-2. Following 14-day isolation and laboratory proven viral clearance, he underwent successful major surgery. He was managed throughout the peri- and post-operative phases without complications or adverse effects on staff. Conclusion: With careful planning, previous coronavirus disease 2019 positive status should not prevent an individual from undergoing successful total laryngectomy and bilateral neck dissection in a safe and timely manner during the pandemic.